Desafios da inclusão para o ensino de química: uma pesquisa ação sobre a inclusão de um aluno com TEA em uma escola na cidade Macapá/AP - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
The monograph addresses the inclusion of students with Autism Spectrum Disorder (ASD) in the school environment, specifically in the teaching of Chemistry. The study investigates whether the subject is taught in an adapted way with inclusive methodologies when there are ASD students in the classroom. The importance of understanding the inclusion of ASD students is highlighted, considering the diversities in the educational environment. The work proposes to identify and analyze the main challenges faced by the teacher and a student with ASD in the teaching and learning process in chemistry teaching. Specific objectives include analyzing school integration, carrying out, evaluating, promoting are strategies. In this context they can be replaced by: investigate/identify; observe; propose reflections on the practice of inclusion based on concrete activities/actions. The research highlights the need for adequate support and professionals prepared to deal with the diversity of students in Chemistry teaching. ASD is characterized by atypical development, challenges in communication and social interaction, repetitive behaviors, varying in intensity levels. The methodology applied was a survey of a high school student with ASD. Observations reveal that there are still needs for adaptations in the physical school environment and in methodologies for teaching chemistry to ASD students
Keywords: Química - Estudo e ensino; Professores e alunos; Transtorno do Espectro Autista; Inclusão; Ambiente escolar; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA